Business ethics ethical decision making and cases - Ferrell, O. C. 1943-; Fraedrich, John 1957-; Ferrell, Linda (Houghton Mifflin Co., 2008)
Using a managerial framework, [the authors] explain how ethics can be integrated into strategic business decisions. This framework provides an overview of the concepts, processes, mandatory, core, and voluntary practices associated with successful business ethics programs.... [The] primary goal ... is to enhance the awareness and the decision-making skills that students will need to make business ethics decisions that contribute to responsible business conduct. By focusing on the concerns and issues of today's challenging business environment, [the authors] demonstrate that studying business ethics provides vital knowledge that contributes to overall business success. -Pref.